Pengaruh Parkir Pada Badan Jalan Terhadap Kinerja Ruas Jalan (Studi Kasus Pada Jalan KH. Wahid Hasyim Kecamatan Sampang Kabupaten Sampang) - Fatah, Wildan; Sudarso, Sudarso; Yusuf A.Q, Andrian Firdaus (Program Studi Teknik Sipil Fakultas Teknik Universitas Palangka Raya, 2024)
One of the big cities in East Java, Sampang Madura, continues to grow. This causes traffic to become increasingly congested in the city. In addition, one of the roads in the city of Sampang, Madura, which is experiencing congestion is Jalan Kh. Wahid Hasyim due to parking on the side of the road which disrupts road performance. The survey was conducted from December 19 to December 25, 2023, for 7 days. Data was collected and processed using the 1997 Indonesian Road Capacity Manual (MKJI). The results showed that on Tuesday, there was a lot of traffic at the location. Side obstacles (1073.7) and road capacity before road parking (6016.8 smp/hour) and after road parking (3439.8) increased significantly. Before the launch of road parking, the road service level was at level C with a V/C value of 0.26 and an average speed of 47.48 km/hour. After the launch, the road service level increased to level C with a V/C value of 0.47 and an average speed of 40.12 km/h. Traffic flow data on Jalan KH Wahid Hasyim is the result of a survey conducted from 06.00 to 18.00 and conducted during rush hour. The traffic flow observed was vehicle traffic with the classification of bicycles, motorbikes, carts, electric bicycles, bentors, passenger cars, cars, pick-ups, buses, trucks, and others